Ramp-edge junctions between superconducting Nd1.85Ce0.15CuO4 and La1.85Sr0.15CuO4. (22nd January 2016) - Hoek, M; Coneri, F; Wang, X Renshaw; Hilgenkamp, H
Abstract: We have fabricated in-plane ramp-edge junctions between Nd1.85 Ce0.15 CuO4 (NCCO) and La1.85 Sr0.15 CuO4 (LSCO) where both layers are superconducting. At the interface, we find an insulating barrier in electronic transport. The barrier is shown to be a tunneling barrier with a combination of inelastic and elastic tunneling, the former is indicated by the appearance of the LSCO phonon density of states in measurements and the latter is inferred from the temperature dependence of the conductance. The energy scale of the barrier is smaller than would be expected from band alignment found by considering the cuprates as degenerate semiconductors. It is closest to the scenario where hybridization of the O 2p valence band states dictate band alignment. Additional experiments with overdoped interlayers of Nd1.8 Ce0.2 CuO4 and La1.75 Sr0.25 CuO4 show that the origin of the barrier is most likely a combination of electronic depletion mainly in the NCCO and a strain effect in the LSCO.